THE EFFECT OF CREDIT RISK AND BANK-SPECIFIC FACTORS ON FINANCIAL PERFORMANCE OF BANKS LISTED IN INDONESIA STOCK EXCHANGE (IDX) - Felle, Aderiana Rosalia; Santioso, Linda (International Journal of Application on Economics and Business, 2024)
The banking industry plays an essential role in national and global economy. It is caused by the intermediation function attached to bank as financial institution. Banks run the intermediation role by pooling funds from depositors and distribute them through credit loan. As business entity, banks have business goal, to enhance their financial performance. Banks gain most of their revenue from their main activity, delivering loan to the debtors. In order to give credit, banks have to deal with the inevitable risk coming along that the debtors might not be able to restore the fund. This risk is known as credit risk. The good credit risk management doesn’t assure the good financial performance. Banks have to fulfill another specific-factors in order to achieve good financial performance. Those factors are effectivity and efficiency of the day- to- day operation and interest pricing strategy. This research is conducted to discover how Non-Performing Loan (NPL), Capital Adequacy Ratio (CAR), Operational Costs on Operating Income (BOPO), Net Interest Margin (NIM), and Loan to Deposit Ratio (LDR) influence the financial performance of Banks Listed in Indonesia Stock Exchange (IDX). The result found that Non-Performing Loan (NPL) and Loan to Deposit Ratio (LDR) have no effect on Banks Financial Performance, Capital Adequacy Ratio (CAR) and Operational Costs on Operating Income (BOPO) have negative effect on Banks Financial Performance, Net Interest Margin (NIM) has positive effect on Banks Financial Performance. From these findings, it can be concluded that to elevate the profitability, banks have to focus on managing the risk management, efficiency, and pricing decision strategy.